Diuretic hormones of Tribolium castaneum (Herbst)(Coleoptera: tenebrionidae) - Cosme, Luciano V. (Kansas State University, 2009)
Neuropeptides are diffusible signal molecules mediating vital physiological processes. We have been interested in a group of neuropeptides and their receptors involved in osmoregulatory neuroendocrine system which has been suggested as a possible target for development of new biopesticides. Since the genome sequence of the T. castaneum has recently been completed, we were able to identify the respective genes encoding three peptide hormones from T. castaneum that were characterized for their diuretic activities in other insects: one calcitonin-like (CT-like DH31) and two corticotropin releasing factor-like (CRF-like DH37 and DH47, the numbers indicates the number of amino acid residues). This peptide is expressed at all developmental stages and in the central nervous system (CNS), Malpighian tubules (MT) and gut. The synthetic peptide TricaDH31 also has been show to be biologically active, inducing significant excretions in adults beetles. When Tcdh31 was silenced using RNAi, adults had deformed wings and abnormal body shape. Mortality in adults was high, the number of eggs laid was reduced as well as the hatchability of the eggs. The two biologically active CRF-like peptides in T. castaneum, are encoded by one gene which undergoes alternative splicing. When Tcdh47 was knocked down, high mortality occurred as well as low oviposition and egg hatchability. Similar effects were observed with silencing of both CRF-like genes. However, RNAi of Tcdh37 transcripts had similar, but less severe effects. Adults also had deformed wings when both CRF-like genes were silenced, but not when just one of them was knocked down. These results indicate that CRF-like genes could have additional biological functions to their roles in dieresis. We tested the in vivo activity of these peptides. TenmoDH47 induced high excretions in adults, whereas TenmoDH37 induces smaller excretions. We identified the respective genes encoding two putative receptors for TricaDH31 as Glean_13321 and Glean_02694 (Trica-ctr1 and Trica-ctr2, respectively) and two receptors for CRF-like peptide as Glean_12799 and Glean_07104 (Trica-crfr1 and Trica-crfr2, respectively). The CT-like receptors are expressed at all developmental stages, in the CNS and MT. RNAi of the receptors revealed that only Trica-ctr2 silencing caused significant mortality and reduction in the number of eggs laid. The CRF-like receptors are expressed at all developmental stages. Adults also had deformed wings and laid fewer eggs after RNAi of Trica-crfr1. RNAi of Trica-crf2 also caused significant mortality. These peptides and receptors seem to fine tune the beetle physiology and may have functions not yet known.
Keywords: Diuretic hormones; Neuropeptides; Tribolium castaneum; Diuretic hormone receptors; Biology, Animal Physiology (0433); Biology, Entomology (0353); Biology, Genetics (0369)